Transformation of Corynespora cassiicola by Agrobacterium tumefaciens. Issue 9 (September 2019) - Li, Junxiang; Hong, Ni; Peng, Bin; Wu, Huijie; Gu, Qinsheng
Abstract: The fungus causing target spot disease, Corynespora cassiicola (Berk. & M. A. Curtis) C. T. Wei, poses an increasing threat to watermelon ( Citrullus lanatus ), muskmelon ( Cucumis melo ), and cucumber ( Cucumis sativus ); the most economically important cucurbit crops grown in China. An understanding of the molecular mechanisms underlying the pathogenicity of C. cassiicola is essential for the development of new strategies to control this disease-causing fungus. Agrobacterium tumefaciens -mediated transformation (ATMT) might be useful to obtain transformants of C. cassiicola, for the ultimate identification of genes involved in pathogenicity. In the present work, we established and optimized an ATMT protocol using A. tumefaciens strain AGL-1 carrying the vector pATMT1 for C. cassiicola . Efficiency of ATMT was 102–148 transformants per 10 6 conidia and successive subculturing of transformants on non-selective and selective media demonstrated that the integrated transfer (T)-DNA was stably inherited in C. cassiicola transformants. The integration of the hygromycin B phosphotransferase ( hph ) gene into C. cassiicola was validated by PCR and Southern blot analyses, which revealed that nearly 90 % of the transformants contained single-copy T-DNA. The transformants with altered phenotypes were characterized. Three of these transformants completely lost pathogenicity and other three showed strongly impaired pathogenicity relative to the Cc -GX strain on muskmelon leaves. These results strongly suggest that ATMT may be used as a molecular tool for identifying genes relevant to pathogenicity in the fungus C. cassiicola, an emerging threat to several agronomically important plants in China. Highlights: Corynespora cassiicola causes target spot disease in cucurbits grown in China. Agrobacterium tumefaciens -mediated transformation (ATMT) was established and optimized for C. cassiicola . Culturing of transformants on non-selective and selective media showed the inserted DNA was stably inherited. Three transformants completely lost pathogenicity on muskmelon leaves. This is the first report of successful ATMT in C.cassiicola .